2013
DOI: 10.1155/2013/857616
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Unsteady Simulation of a Counterrotating Aspirated Compressor with a Focus on the Aspiration Slot and Plenum

Abstract: An unsteady analysis of the MIT counterrotating aspirated compressor (CRAC) has been conducted using the Numeca FINE/Turbo 3D viscous turbulent flow solver with the Nonlinear Harmonic (NLH) method. All three blade rows plus the aspiration slot and plenum were included in the computational domain. Both adiabatic and isothermal solid wall boundary conditions were applied and simulations with and without aspiration were completed. The aspirated isothermal boundary condition solutions provide the most accurate rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The Spalart-Allmaras (SA) one-equation model is adopted to model the turbulent fluctuations due to its robustness and ability to treat the complex flows at high Mach number condition, and specially, it also presents a good capability to simulate the flow fields within the aspiration device, 9 which would be beneficial to describe the flow details at the interface between the aspiration device and mainflow passage more accurately and hence to give a reasonable prediction on the aspiration effects. Previous studies [8][9][10] on the aspirated compressor and aspirated cascade have demonstrated that the results predicted by the SA turbulence model could present a much better match with the experimental data, and besides, this model has also been applied to analyze 3D flow in the TB. 12,13,15 To accelerate the convergence, multigrids technique, local time stepping and an implicit residual smoothing procedure are used.…”
Section: Verification Of Cfc Cfd Setupmentioning
confidence: 95%
See 2 more Smart Citations
“…The Spalart-Allmaras (SA) one-equation model is adopted to model the turbulent fluctuations due to its robustness and ability to treat the complex flows at high Mach number condition, and specially, it also presents a good capability to simulate the flow fields within the aspiration device, 9 which would be beneficial to describe the flow details at the interface between the aspiration device and mainflow passage more accurately and hence to give a reasonable prediction on the aspiration effects. Previous studies [8][9][10] on the aspirated compressor and aspirated cascade have demonstrated that the results predicted by the SA turbulence model could present a much better match with the experimental data, and besides, this model has also been applied to analyze 3D flow in the TB. 12,13,15 To accelerate the convergence, multigrids technique, local time stepping and an implicit residual smoothing procedure are used.…”
Section: Verification Of Cfc Cfd Setupmentioning
confidence: 95%
“…The FNM does not require the exact matching of the grid points distributions between the two domain sides and is often used in the numerical studies on the casing treatments and aspirated compressors. [8][9][10] For a highly loaded aspirated outlet vane, poorer inlet conditions would aggravate the endwall flow and hence might require a more complex EBLS scheme to suppress it. Therefore, like the aspirated compressor designed by MIT, 5 additional circumferential aspiration slots should also be implemented in front of the blade so as to control the inlet boundary layer thickness within reasonable range.…”
Section: Verification Of Cfc Cfd Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Isomura et al [2] was looking at a small centrifugal compressor where heat transfer effects become important due to the small size. Kerrobrock et al [3] commented that heat transfer was possibly important in a compressor blow down facility, and Knapke (with others) [4,5,6] looked into modeling that heat transfer as part of an unsteady simulation. A study by Bruna and Turner [7] [8] looked at CFD modeling of NASA rotor 37 where a simulation did a much better job of matching the temperature profiles and efficiency when heat transfer was accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…After closing the bleeds the compressor stalled immediately, and was unable to recover from stall without bleeding restored (regardless the value of applied back pressure) [1]. Some other studies [2][3][4] showed also the possibility of boosting axial compressor performance by the removal of boundary layer flows in regions prone to flow separations. The problem with controlling boundary layer flows by bleeding is the removal of few percent of flux on each stage.…”
mentioning
confidence: 99%